2000
DOI: 10.2165/00002018-200023020-00003
|View full text |Cite
|
Sign up to set email alerts
|

A Risk-Benefit Assessment of Injections of Hyaluronan and its Derivatives in the Treatment of Osteoarthritis of the Knee

Abstract: Hyaluronan is critical for the homeostasis of the joint as an organ, in part, because it provides the rheological properties (viscosity and elasticity) of the synovial fluid. These properties depend upon both the concentration and the molecular weight of the hyaluronan in the synovial fluid. In osteoarthritis, the hyaluronan is both smaller in size and lower in concentration. Thus, it is rational and physiologically meaningful to treat osteoarthritis with viscosupplementation, i.e. injection of material design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
76
0
15

Year Published

2002
2002
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(94 citation statements)
references
References 41 publications
3
76
0
15
Order By: Relevance
“…Although HA is widely used in the treatment of OA, [12][13][14] the nature of its anti-inflammatory mechanism remains poorly understood. 11 Similarly, a clinical benefit of HA in rotator cuff disease was demonstrated by Shibata et al, 15 although little is known about its anti-inflammatory effect in the disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although HA is widely used in the treatment of OA, [12][13][14] the nature of its anti-inflammatory mechanism remains poorly understood. 11 Similarly, a clinical benefit of HA in rotator cuff disease was demonstrated by Shibata et al, 15 although little is known about its anti-inflammatory effect in the disease.…”
Section: Discussionmentioning
confidence: 99%
“…11 Intraarticular HA injection is used to treat knee OA, and its therapeutic efficacy has been verified. [12][13][14] In rotator cuff disease, Shibata et al uniquely demonstrated that HA injection is an effective conservative procedure, 15 although the mechanism of its anti-inflammatory effect is not fully understood.…”
mentioning
confidence: 99%
“…The advantage of cross-linkage seems mainly to increase the stability and residence time of the VS in the joint. However, other studies suggest the noncross-linked VS effect is comparable with that of the cross-linked system [27,43], and to date, no definitive conclusion has been reached regarding any advantage of cross-linkage on the clinical benefit [2,27,29,33,52,59]. Therefore, techniques aimed at investigating variations of HA (concentration and molecular weight) and rheologic changes attributable to VS are needed to better understand its mechanisms of action and to determine possible differences between different HA commercial formulations.…”
Section: Introductionmentioning
confidence: 99%
“…Existem no mercado vários preparados de ácido hialurônico e as suas diferentes propriedades reológicas são dependentes basicamente de seus pesos moleculares (8) . Com um peso molecular de 6x10 6 daltons (Da), as propriedades viscoelásticas do Hylan G-F 20 são similares às do líquido sinovial de adultos jovens saudáveis (3) ; três injeções semanais são comprovadamente seguras e superiores em eficácia em relação ao placebo (infiltração com solução salina ou artrocentese) (9,10) com analgesia de até seis meses.…”
Section: áCido Hialurônicounclassified